Large-scale zygosity testing using single nucleotide polymorphisms. - Hannelius, U; Gherman, L; Mäkelä, V; Lindstedt, A; Zucchelli, M; Lagerberg, C; Tybring, G; Kere, J; Lindgren, C (2007)
A requirement for performing robust genetic and statistical analyses on twins is correctly assigned zygosities. In order to increase the power to detect small risk factors of disease, zygosity testing should also be amenable for high throughput screening. In this study we validate and implement the use of a panel of 50 single nucleotide polymorphisms (SNPs) for reliable high throughput zygosity testing and compare it to a panel of 16 short tandem repeats (STRs). We genotyped both genomic (gDNA) and whole genome amplified DNA (WGA DNA), ending up with 47 SNP and 11 STR markers fulfilling our quality criteria. Out of 99 studied twin pairs, 2 were assigned a different zygosity using SNP and STR data as compared to self reported zygosity in a questionnaire. We also performed a sensitivity analysis based on simulated data where we evaluated the effects of genotyping error, shifts in allele frequencies and missing data on the qualitative zygosity assignments. The frequency of false positives was less than 0.01 when assuming a 1% genotyping error, a decrease of 10% of the observed minor allele frequency compared to the actual values and up to 10 missing markers. The SNP markers were also successfully genotyped on both gDNA and WGA DNA from whole blood, saliva and filter paper. In conclusion, we validate a robust panel of 47 highly multiplexed SNPs that provide reliable and high quality data on a range of different DNA templates.